Direct-write piezoelectric ultrasonic transducers for pipe structural health monitoring. (October 2019) - Guo, Shifeng; Chen, Shuting; Zhang, Lei; Liew, Weng Heng; Yao, Kui
Abstract: Novel direct-write ultrasonic transducers comprising piezoelectric poly(vinylidenefluoride/trifluoroethylene) [P(VDF/TrFE)] polymer coatings which were in-situ deposited, crystallized and patterned on pipe for structural health monitoring purpose. Lamb ultrasonic wave signals, generated and measured by the direct-write transducers and propagating along the pipe structure, were used to monitor the integrity of the pipe structure. The experimental measurements of the axial Lamb wave on pipe structure showed the substantial reduction in the ultrasonic signal by the defects. In addition, pipe thickness was accurately determined with the direct-write transducers to generate and detect the ultrasonic wave in the pipe thickness direction using pulse-echo mode. Our result and analyses suggest that implementation of the unique direct-write ultrasonic transducer technology is promising for realizing structural health monitoring for pipeline structures with improved consistency and reliability.